The Effectiveness of Project Based Learning Ecosystems Dioramas with Jelajah Alam Sekitar Approach against Students' Critical Thinking Ability and Creativity - Kurniyanti, Ratih; Tri Martuti, Nana Kariada; Alimah, Siti (Journal of Biology Education, 2019)
The purpose of this study was to analyze the effectiveness of Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach against students’ critical thinking ability and creativity, and to analyze the relationship between critical thinking ability and students' creativity in Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach. This research method is pre-experimental design with pre-test and post-test one group design. The results showed that Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach was effective against students' critical thinking ability and creativity. The average of critical thinking ability in post-test is 84.96 and average of creativity in post-test is 84.50. The completeness of classical learning shows "High" criteria, the classical completeness rate in post-test of critical thinking and creativity is same (89.21%). The results of the N-gain mean on the test scores of critical thinking ability and creativity are in the "High" criteria. N-gain of critical thinking ability shows "High" category (66.66%) and N-gain creativity shows "High" category (79.42%). The results of the analysis of the two average difference test (one right side) on the critical thinking ability test has t table of 1.97 < t count of 20.89. The creativity test has t table of 1.97 < t count of 31.80, so it shows a significant difference between the achievements at the pre-test and post-test. Based on these results it can be concluded that the Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach are effective against students' critical thinking ability and creativity. The relationship between critical thinking ability and creativity shows the relation of 0.38, has a "Low" criteria, so it can be concluded that the relationship between critical thinking ability and student creativity in Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach is low.